2019
DOI: 10.1371/journal.pone.0222717
|View full text |Cite
|
Sign up to set email alerts
|

Adverse prognosis of glioblastoma contacting the subventricular zone: Biological correlates

Abstract: IntroductionThe subventricular zone (SVZ) in the brain is associated with gliomagenesis and resistance to treatment in glioblastoma. In this study, we investigate the prognostic role and biological characteristics of subventricular zone (SVZ) involvement in glioblastoma.MethodsWe analyzed T1-weighted, gadolinium-enhanced MR images of a retrospective cohort of 647 primary glioblastoma patients diagnosed between 2005–2013, and performed a multivariable Cox regression analysis to adjust the prognostic effect of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 57 publications
7
45
0
2
Order By: Relevance
“…demonstrated that the subventricular zone of the brain can modulate GBM microenvironment and take part in MES transformation through C/EBP‐ β signaling. [ 52 ] Another study reported that transglutaminase 2 (TGM2) can act as a mediator of mesenchymal transformation in perinecrotic regions of GBM by inducing C/EBP‐ β expression through GADD153 (a transcriptional inhibitor of C/EBP β signaling) degradation. [ 53 ] Accumulating evidence demonstrated the role of STAT3 in PMT.…”
Section: Molecular Mechanisms Of Mesenchymal Transformation In Gbmmentioning
confidence: 99%
“…demonstrated that the subventricular zone of the brain can modulate GBM microenvironment and take part in MES transformation through C/EBP‐ β signaling. [ 52 ] Another study reported that transglutaminase 2 (TGM2) can act as a mediator of mesenchymal transformation in perinecrotic regions of GBM by inducing C/EBP‐ β expression through GADD153 (a transcriptional inhibitor of C/EBP β signaling) degradation. [ 53 ] Accumulating evidence demonstrated the role of STAT3 in PMT.…”
Section: Molecular Mechanisms Of Mesenchymal Transformation In Gbmmentioning
confidence: 99%
“…Two of them demonstrate a correlation with increased glioblastoma expression of CD133, a glioma stem cell marker, with proximity to the VSVZ (20,21). However, large bulk tissue analyses have not revealed a consistent molecular signature of VSVZ-contacting glioblastomas (9,10). Therefore, the role of the microenvironment of the VSVZ is also being probed to understand the increased malignancy of glioblastomas with VSVZ contact.…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastomas with and without VSVZ invasion or contact are not genomically distinct in bulk profiling (9,10). Therefore, the more severe clinical phenotype of those patients is likely due t o t h e m i c r o e n v i r o n m e n t o f t h e V S V Z ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Hallaert et al [ 80 ] also observed that the connection of GBM to the sub-ventricular zone appears to be a novel, independent risk factor leading to a worse prognosis. An association between sub-ventricular zone contact and markers related to the epithelial–mesenchymal transition was discovered [ 81 ]. Moreover, there is a definite influence of the tumor and the response to treatment on the systemic immune and inflammatory compartments [ 34 ].…”
Section: Immunotherapy For Gbmmentioning
confidence: 99%